Pengaruh Pupuk Amonium Klorida terhadap N-Total Tanah, Serapan N, dan Hasil Jagung Manis (Zea Mays Saccharata Sturt) pada Inceptisol Jatinangor - Futri Fauziah; Emma Trinurani Sofyan; Ade Setiawan; Dirga Sapta Sara; Warid Ali Qosim (Fakultas Pertanian Universitas Padjadjaran, 2021)
In the past decade, Indonesian interest towards sweet corn has increased. This condition creates a wide market opportunity for sweet corn. However, sweet corn cultivation in Indonesia is often constrained by low soil fertility. One of the essential nutrients needed by sweet corn is nitrogen. Nitrogen can be obtained from inorganic fertilizers such as Ammonium Chloride (NH4Cl) fertilizer. This research aimed to determine the effect and the best dosage of Ammonium Chloride (NH4Cl) in increasing N-total, N uptake, and yield of Sweet Corn (Zea mays saccharata Sturt) of Talenta variety on Jatinangor Inceptisol. This experiment was conducted at the research field of Soil Chemistry and Plant Nutrition, Department of Soil Science and Land Resources, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor from July to October 2020. The experimental design used in this research was Randomized Block Design (RDB), which consisted of nine treatments with 1 control treatment (without fertilizer), 1 standard single N, P, K fertilizer treatment, 3 dosages of Ammonium Chloride (NH4Cl) fertilizer treatment, and 4 combinations of Ammonium Chloride (NH4Cl) fertilizer with ¾ recommended dose of standard N, P, K fertilizer. The results showed that the combination of Ammonium Chloride (NH4Cl) fertilizer affected the total Nitrogen content, nitrogen uptake, and yield of sweet corn. Combination of 1 ¼ dose of Ammonium Chloride (NH4Cl) fertilizer with ¾ recommended dose of standard N, P, K fertilizer show the highest increase in total nitrogen (0,24%), nitrogen uptake (2,72 g per plant), and fresh weight of the corn cobs (0,42 kg per plant).